Ten good and bad things about my life (so far) - Martin, Ann M., 1955- (Feiwel & Friends, 2012)
Pearl writes an essay about her complicated summer during which her father lost his job, her sister was her junior camp counselor, and she had an explosive fight with James Brubaker the Third.